Influence of Co concentration on the structural, optical, morphological and photo-diode properties of cerium oxide thin films. Issue 11 (15th August 2016) - Suresh, R.; Ponnuswamy, V.; Sankar, C.; Manickam, M.; Mariappan, R.
Abstract: Highly uniform and well-dispersed ring shaped particles of CDC (Cobalt doped cerium oxide) films are successfully deposited by Nebulizer Spray Pyrolysis (NSP) technique. The structural, morphological, optical and photo-diode properties of the films are investigated. Cubic fluorite crystallites are detected by X-ray diffraction pattern with preferred orientation along (111) direction. Co concentrations distress the crystallinity and structural parameters. The transmittance decreases with increasing Co concentration due to the presence of covalent bonds between cerium and oxygen. PL spectra revealed that three consistent sharp and broad peaks observed at 369 (3.31 eV), 394 (3.14 eV) and 425 nm (2.91 eV) correspond to near-band-edge emission (NBE) in UV region, deep level emission (DLE) in violet and blue of the visible region respectively. The deep level emissions result from the recombination of electrons with holes trapped in singly ionized oxygen vacancies (Vo+). Large agglomerated ring, button and spherical crystallites are obtained with the typical size in the range 83–207 nm. XPS analysis exhibits the presence of Ce, Co, O, C and Na in the films that indicates the non-stoichiometric behavior. I-V characteristics show the rectifying nature with a typical forward to reverse current ratio of ~7 in the range −4 to +4 V. The turn-on voltage of the hetero-junction is found to be ~1.7 V. The transient photocurrent behavior indicates that the device has a good stability and quick response to suggests that the prepared heterojunction device can be used as a white light photodetector and UV detector applications.